MOSQUE CLEANLINESS MANAGEMENT AS A MEANS TO IMPROVE ENVIRONMENTAL CLEANLINESS IN AL MADINAH AL MUNAWAROH MOSQUE: PENGELOLAAN KEBERSIHAN MASJID SEBAGAI SARANA UNTUK MENINGKATKAN KEBERSIHAN LINGKUNGAN DI MASJID AL MADINAH AL MUNAWAROH - Ferdiyansyah Ferdiyansyah; Yafta Qisti; Jemson Sihombing (Yayasan Education and Social Center, 2022)
The mosque is one of the important elements in the structure of Islamic society. The mosque for Muslims has a great meaning in life, both physical and spiritual meaning. The mosque is used as a place of worship for Muslims to perform prayers. In the activities or implementation of prayer it is very obligatory to perform ablution and of course the place of worship must be kept clean. Of course, in terms of the cleanliness of the mosque, there are still many that are not clean, from the cleanliness of fans, air conditioners, floors, ceilings, mirrors and the surrounding yard. Especially in places where the cleanliness of the mosque is still not paid attention to, this condition is a concern for the local community so that the cleanliness of the mosque is maintained while carrying out prayers. Carrying out community service at the mosque is a solution that can be carried out routinely to maintain the cleanliness and comfort of the mosque